Inklusion mit Blick auf Kinder mit Behinderungen - Albers, Timm (Inklusion und Partizipation 2015)

Vorwort - Albers, Timm (Ohren Spitzen in der Krippe)

Vom Alten Reich zum Deutschen Bund 1789–1815 - Süßmann, Johannes

Einleitung [zur Sektion III: Subjektkonstitution, soziale Praktiken und fremde Dinge] - Süßmann, Johannes (Präsenz und Evidenz fremder Dinge im Europa des 18. Jahrhunderts)

Der Garten als Bauakt. Zur Einrichtung ›natürlicher‹ Herrschaft in der Wörlitzer Landschaftsarchitektur - Süßmann, Johannes (Politische Gartenkunst? Landschaftsgestaltung und Herrschaftsrepräsentation des Fürsten Franz von Anhalt-Dessau in vergleichender Perspektive: Wörlitz, Sanssouci und Schwetzingen)

Die Franckeschen Stiftungen als Bauakte. Eine Analyse ihrer Pragmatik - Süßmann, Johannes (tief verwurzelt – hoch hinaus. Die Baukunst der Franckeschen Stiftungen als Sozial- und Bildungsarchitektur des protestantischen Barock. [Katalog der Jahresausstellung der Franckeschen Stiftungen vom 12. September 2015 bis 21. Februar 2016])

The Francke Foundations as ›Building Acts‹. An Analysis of their Pragmatics - Süßmann, Johannes (strong roots – inspiring vision. The Francke Foundations as Social and Educational Architecture in the Protestant Baroque)

Early Prediction of Security Properties for Mechatronic Systems - Schwichtenberg, Bahar
Mechatronic systems are used more than ever in human life. They can be found in a very wide range of domain contexts, from household appliances, and cars, to medical equipment. Mechatronic systems, as a kind of embedded systems, are the tight integration of mechanical and electrical engineering, which embed software systems. Information security of mechatronic systems has not received much attention yet. However, wherever data exists, cyber attacks threaten mechatronic systems. The thesis focuses on the early design stages of the development of mechatronic systems. Model sequence diagrams (MSDs) are used to model requirements with real-time and safety properties. In this thesis, MSDs are extended such that security properties for example authenticity and privacy can be modeled and analyzed automatically.
Keywords: Software Architecture; Requirements Engineering; Embedded Systems

Entscheidungen im professionellen Handeln von Pädagoginnen und Pädagogen - van Ophuysen, Stefanie; Bloh, Bea; Bellmann, Johannes (Entscheidung)

‘Light of Life’: Gender, Place and Knowledge in H. G. Wells’ 'Ann Veronica' - Mildorf, Jarmila (Dark Nights, Bright Lights)

Worth Pursuing? The Limits of Cognitive Narratology - Mildorf, Jarmila (Književna istorija / Literary History)

Unreliability in Patient Narratives: From Clinical Assessment to Narrative Practice - Mildorf, Jarmila (Unreliable Narration and Trustworthiness: Intermedial and Interdisciplinary Perspectives)

„Leider sind wir bankrott“. Zahlungsausfälle in der Geschichte Griechenlands im 19. und 20. Jahrhundert - Schönhärl, Korinna (Die Krise in Griechenland. Ursprünge, Verlauf, Folgen)

Projektorientiertes Lernen im bildungswissenschaftlichen Studienanteil der universitären Lehrer*innenausbildung. Erfahrungen in demokratiepädagogisch ausgerichteten Lernsettings - Göhler, T.; Schlüter, M.; Stroot, T.; Westphal, Petra (Differenz erleben - Gesellschaft gestalten. Demokratiepädagogik in der Schule)

Den individuellen Lernprozess der Studierenden im Blick: Anders betreuen in modernen Laborpraktika - Probst, Heike M.; Sacher, Marc; Schaper, Niclas (Mittendrin - Lehre im Dialog)

Neue Wege zur Konzeption eines kompetenzfördernden, studierendenzentrierten Laborpraktikums - Sacher, Marc (Mittendrin - Lehre im Dialog)

Symmetry exploiting control of hybrid mechanical systems - Flaßkamp, K.; Hage-Packhäuser, S.; Ober-Blöbaum, Sina (Journal of Computational Dynamics)

Discrete variational Lie group formulation of geometrically exact beam dynamics - Demoures, F.; Gay-Balmaz, F.; Leyendecker, S.; Ober-Blöbaum, Sina; Ratiu, T.S.; Weinand, Y. (Numerische Mathematik)
Keywords: 53D05; 65P10; 74B20; 74H15

High order variational integrators in the optimal control of mechanical systems - Campos, C. M.; Ober-Blöbaum, Sina; Trélat, E. (Discrete and Continuous Dynamical Systems)

Relaxing mixed integer optimal control problems using a time transformation - Ringkamp, M.; Ober-Blöbaum, Sina; Leyendecker, S. (Proceedings of Applied Mathematics and Mechanics)